Memaknai Kembali Spiritualitas Islam Dalam Peradaban Kontemporer - Baedhowi Baedhowi (Millah: Journal of Religious Studies, 2004)
This article tries to describe the reinterpretation of  the Islamic spirituality in contemporary era. The writer explores the short history in sufism as a source of  Islamic spirituality. He also wants to explore how to interprete the sufism as a product of  history. From its history, we can know the development of  sufisme period to period. In other hand, we can also reinterprete the meaning of  Islamic spirituality in the contemporary civilization or modernism point of  view. For example, we can know how to reinterprete the concept o f  “wahdat al-wujud” and “wahdat al-adyan” as a main part of  spirituality in Islam. This reinterpretation is expected to contribute the moral ethic or spirituality in contemporary era.